2014
DOI: 10.3748/wjg.v20.i20.5935
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for hepatocellular carcinoma recurrence

Abstract: The recurrence of hepatocellular carcinoma, the sixth most common neoplasm and the third leading cause of cancer-related mortality worldwide, represents an important clinical problem, since it may occur after both surgical and medical treatment. The recurrence rate involves 2 phases: an early phase and a late phase. The early phase usually occurs within 2 years after resection; it is mainly related to local invasion and intrahepatic metastases and, therefore, to the intrinsic biology of the tumor. On the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
127
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 129 publications
(226 reference statements)
6
127
3
Order By: Relevance
“…The fi ndings of the present study demonstrated an inverse association between tumor number and DFS time following initial TACE. Consistent with the present study, several previous studies have identified tumor number as a predictor of intrahepatic recurrence following initial TACE for HCC (27)(28)(29)(30)(31). Recurrence following initial remission by TACE has been more often reported in patients with multinodular-type HCC and with portal vein thrombosis (32).…”
Section: Discussionsupporting
confidence: 79%
“…The fi ndings of the present study demonstrated an inverse association between tumor number and DFS time following initial TACE. Consistent with the present study, several previous studies have identified tumor number as a predictor of intrahepatic recurrence following initial TACE for HCC (27)(28)(29)(30)(31). Recurrence following initial remission by TACE has been more often reported in patients with multinodular-type HCC and with portal vein thrombosis (32).…”
Section: Discussionsupporting
confidence: 79%
“…HCC has the third highest mortality rate worldwide, with the 5-year survival rate ranging from 10 to 28% [2,3]. Multiple factors are associated with clinical outcomes of HCC, including liver function, tumor site, treatment type, and comorbidity [4,5]. Early detection and referral for curative treatments such as surgical resection and radiofrequency ablation are the most effective approaches to increase the survival of patients.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, survival rate is only 30-50% over the same period of time [5,6]. When HCC recurs more than 2 years after LR, this is mainly due to the emergence of new neoplastic lesions, as a consequence of the carcinogenic environment of the remnant liver [7][8][9]. However, recurrence after LR may occur earlier (within 2 years).…”
Section: Introductionmentioning
confidence: 99%